PERCEPTION OF PICTORIAL HEALTH WARNING ON CIGARETTE PACKS, SMOKING BEHAVIOUR AND WANT TO QUIT SMOKING AMONG STUDENTS UNDERGRADUATE OF STATE ISLAMIC UNIVERSITY OF NORTH SUMATERA, INDONESIA - Nasution, Fauziah; Tarigan, Azhari Akmal; Siregar, Putra Apriadi; Marpaung, Watni (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Pictorial health warning on cigarette packs has been implemented since 2014, but smokers in Indonesia increase every years. Pictorial health warning on cigarette packs must be continuously evaluated regarding its effectiveness in reducing smoking behavior in Indonesia. Regulated about Regulations of pictorial health warning on cigarettes packs are expected to make smokers to quit smoking and regulations that have been in effect since 2014 should have been evaluated to see pictorial health warning on cigarettes packs that can change the behavior of smokers or prospective smokers in adolescents. This study aims to describe perceptions of pictorial health warning on cigarette packs and smoking behavior and intention to quits smoking of undergraduate student of state Islamic University of North Sumatra. Methodology: This research was conducted to students of the Islamic University of North Sumatra as many as 215 students. The study was conducted in March 2019 using a structured questionnaire that had been prepared. The data in this study will be presented in the form of frequency distributions and then the results are presented in the table. Results: The results of this study indicate that the respondents felt not fear with pictorial health warning on cigarette packs as many as 165 people (76.7%). For the smoking behavior of students it was found that as many as 147 people (68.4%) stated that they had not smoking and respondents who stated smokers as many as 68 people (31.6%), wanted to stop smoking after seeing picture health warning on cigarette packaging as many as 28 people (41.2%). Respondents who said they would continue smoking even though they had seen pictorial health warning on cigarette packs as many as 40 people (58.8%). Conclusion: The majority of students undergraduates of the North Sumatra State Islamic University (UIN SU) were not afraid when they saw pictorial health warning on cigarette packs and students undergraduates have smoking behaviour. Those who smoke said they wanted to stop smoking after seeing pictorial health warning on cigarette packs especially when looking at ppictorial health warning on cigarette packs related to smoking resulting in lung cancer.